KNOWLEDGE MANAGEMENT IN SCHOOL LIBRARIES IN INDONESIA - Rosiana Nurwa Indah; Wira Puji Hendarwati; Majidah Majidah (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
This study aims to analyze the implementation of knowledge management (KM) in school libraries in Indonesia, focusing on three key indicators: people (human resources), process, and technology. Using a mixed-methods approach with an explanatory sequential design, data were collected from 399 respondents via a questionnaire and supplemented with interviews and observations. The results indicate that KM implementation generally falls into the “good” category with a grand mean of 3.65. The “people” indicator received the highest score (4.03), followed by the “process” indicator (3.79), while the “technology” indicator received the lowest score (3.15). These findings reveal an imbalance in the knowledge ecosystem; although librarians and educational staff demonstrate high proactivity in sharing knowledge, technological infrastructure support remains limited to basic administrative functions and has not yet reached the level of a systematic knowledge repository. The lack of technological support results in KM practices in school libraries being person-dependent (relying on individuals), thereby risking the creation of “ephemeral knowledge” that is easily lost during staff turnover. This study concludes that policy reforms are needed to prioritize the standardization of digital infrastructure and the enhancement of librarians’ digital competencies in order to transform school libraries from collection circulation units into institutional memory centers.